A South African perspective on work-life balance: a look at women in academia - Segal, Jenna (My University, 2014)
Work-life balance has been a topic of researched for over two decades. The primary aim of the current research project was to explore the challenges and issues that female academics (in the context of a South African University) face in balancing their work roles and their non-work roles and responsibilities. The study explored female academics’ perceptions of the relevance and effectiveness of policy aimed to promote work-life balance. The research utilised a qualitative approach to explore the topic of work-life balance – the research instrument being a semi-structured interview. Boundary Theory was incorporated into the study as the overarching theory in comprehending the construct of work-life balance and as the basis for the Thematic Content Analysis. The data revealed that as an occupation, academia provides a large degree of flexibility and participants reported this as both helpful in the achievement work-life balance and complicit in the creation of conflict between the work and non-work domains. Overall there was a trend for the participants to have more role integration as a result of highly flexible and permeable boundaries. The relevance of role identity in the negotiation and maintenance of boundaries was a particularly prominent aspect of the data that assisted in understanding the participants’ experiences of work-life balance. According to several participants’ reports, the role of the institution’s policies is integral in the achievement of work-life balance. However there was a great deal of variation in the reports of the role of the institution’s policies – some positive and others negative. In general the participants were not clear on the role that the South African Government plays in the achievement of work-life balance.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Industrial/Organisational Psychology, 2013